Hepatoprotective effect of hydroalcoholic extract of Desmodium molliculum (“manayupa”) in rats with hepatic intoxication induced by paracetamol - Saucedo Estela, Pamela Yanina (2019)
Objective: To determine the hepatoprotective effect of the hydroalcoholic extract of Desmodium molliculum (“manayupa”) at different concentrations (50, 500 and 800 mg/kg), and also to evaluate its active metabolites. Materials and Methods: Hydroalcoholic extract of D. molliculum was applied to Holtzman rats randomized into six groups (n = 5), which received the following treatments, for ten days, via peroral: groups I and II: physiological serum 10 mL/kg; group III: silymarin 100 mg/kg; Group IV: 50 mg/kg; group V: 500 mg/kg and group VI: 800 mg/kg of the hydroalcoholic extract. On the sixth day of treatment, rats from groups II to VI received paracetamol at 400 mg/kg perorally, with one hour difference from previous treatment, until complete ten days. Results: According to the doses administered, it was observed that the extract of 500 mg/kg and 800 mg/kg of the hydroalcoholic extract showed the largest hepatoprotective effect. Conclusions: The hydroalcoholic extract of Desmodium molliculum (“manayupa”) showed an hepatoprotective effect.